2021
DOI: 10.1093/cid/ciab260
|View full text |Cite
|
Sign up to set email alerts
|

Breast Milk Antibody Levels in Tdap-Vaccinated Women After Preterm Delivery

Abstract: Introduction/Background & Aims Enrichment of breast milk (BM) with immunoglobin (Ig)A and IgG, through maternal vaccination, could help young infants combat targeted pathogens. However, evidence on this effect after preterm delivery is lacking. This study investigated the total and anti-pertussis toxin (anti-PT) specific IgA and IgG production in BM after term or preterm delivery in the presence of maternal Tdap (tetanus, diphtheria, acellular pertussis) vaccination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…In contrast to the IgA-dominant antibody response in the milk of women previously infected with SARS-CoV-2 ( Fox et al, 2020 ), our results indicate that the post-vaccine antibody response in human milk is IgG dominant. This is consistent with previously published studies about SARS-CoV-2 vaccination ( Gray et al, 2021 ; Perl et al, 2021 ) and has also been observed after Tdap vaccination in pregnancy ( Orije et al, 2021 ). One potential explanation for this difference is that vaccinated mothers are exposed to viral antigen via intramuscular injection, whereas infected mothers have immunological education occurring in the mucosa, where IgA plays a greater role.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to the IgA-dominant antibody response in the milk of women previously infected with SARS-CoV-2 ( Fox et al, 2020 ), our results indicate that the post-vaccine antibody response in human milk is IgG dominant. This is consistent with previously published studies about SARS-CoV-2 vaccination ( Gray et al, 2021 ; Perl et al, 2021 ) and has also been observed after Tdap vaccination in pregnancy ( Orije et al, 2021 ). One potential explanation for this difference is that vaccinated mothers are exposed to viral antigen via intramuscular injection, whereas infected mothers have immunological education occurring in the mucosa, where IgA plays a greater role.…”
Section: Discussionsupporting
confidence: 93%
“…85,102,112,113 It has been documented that inactivated influenza virus vaccine, 23-valent pneumococcal polysaccharide vaccine, and meningococcal vaccine, induced five times stronger specific antibody levels in milk until the 2nd month postpartum, and high specific IgM levels in milk up to 6 months postpartum compared with a non-vaccinated group. 114,115 Moreover, vaccinationinactivated SARS-CoV-2 and influenza vaccines during pregnancy and lactation increased specific levels of IgA in milk. 116,117 Another study revealed that maternal immunization against Streptococcus pneumoniae increased the IgG levels in human milk and protected the infant against infection.…”
Section: G Ene Ti C Chang E S In Mammary G L Ands and Milk Comp Os It...mentioning
confidence: 99%
“…Studies have shown that the administration of vaccines during pregnancy might produce specific IgG in breast milk for periods ranging from 12 weeks to 1 year postpartum 85,102,112,113 . It has been documented that inactivated influenza virus vaccine, 23‐valent pneumococcal polysaccharide vaccine, and meningococcal vaccine, induced five times stronger specific antibody levels in milk until the 2nd month postpartum, and high specific IgM levels in milk up to 6 months postpartum compared with a non‐vaccinated group 114,115 . Moreover, vaccination‐inactivated SARS‐CoV‐2 and influenza vaccines during pregnancy and lactation increased specific levels of IgA in milk 116,117 .…”
Section: Genetic Changes In Mammary Glands and Milk Composition After...mentioning
confidence: 99%
“…Further, infants with pertussis whose mothers received the TdaP vaccine had lower risks of hospitalization, ICU admission, and shorter hospital stays compared to mothers who were not vaccinated ( 71 ). In summary, vaccination with Tdap during or shortly after pregnancy greatly increases the level of anti-PT antibodies in human milk ( 64 66 , 72 , 73 ) and may contribute to the protection provided to the infant against pertussis infection.…”
Section: Antibody Composition In Human Milk Post-influenza and Pertus...mentioning
confidence: 99%